Pengembangan UMKM Keripik Ikan Lele Berbasis Inovasi Produk, Sertifikasi Legalitas, dan Strategi Pemasaran Di Desa Tangsil Wetan Bondowoso - Ansori Ansori; Hosaini Hosaini (Jurnal Medika: Medika, 2025)
Small and Medium Enterprises (SMEs) in Tangsil Wetan Village are diverse, ranging from street vendors and street vendors to local product marketers. Most residents are farmers who rely solely on a 3–4-month harvest, while others are freshwater fish farmers (pokdakan). Given this situation, an initiative emerged to incorporate these businesses into the Student Creativity Program (PKM) so that fish farmers like Mr. Muzayyin and his group can further develop. The PKM aims to provide solutions to the still-conventional catfish processing and marketing system by offering innovative, tastier, more varied, and competitive catfish chips. Furthermore, the PKM aims to train production skills, marketing management, and business legality through the creation of NIB (National Business License) and PIRT (Farm Business License), while also strengthening business capital with support from the Village-Owned Enterprise (BumDes). The PKM method was carried out over two months (August–September 2023) and involved eight members. The activity began with an interview with the Head of the Fish Farmers Association, followed by permit processing, material and non-material preparation, and the formation of a coordination team. Following this, training was conducted on catfish chip production, marketing management, and business licensing. The results and discussion demonstrated the farmers' openness in addressing issues and their enthusiasm for participating in discussions. The mentoring improved their understanding of product innovation and online marketing. After the program, the group demonstrated growth potential of up to 80% and began collaborating with other parties. Conclusions and Implications: This PKM not only helps increase the added value of catfish through chip products, but also encourages business independence, expands the market, and creates new job opportunities that support the economy of Tangsil Wetan Village.